DIGITAL VISUAL MERCHANDISING STRATEGIES AND SMART MARKET PLATFORM ADOPTION AMONG TRADITIONAL MARKET MSMES IN PADANG - Liza Yuliana; Liesma Maywarni Siregar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Traditional markets face a critical competitive disadvantage in the digital economy due to poor digital touchpoints and user experience misalignment. This study aims to evaluate the distinct impacts of digital visual merchandising (DVM) configurations on smart market platform adoption (SMPA) among traditional market MSMEs in Padang, West Sumatra. Utilizing an extended Technology Acceptance Model (TAM) as the structural framework, this research adopts a deductive quantitative design. Primary data was gathered from 150 eligible merchants across Pasar Raya, Pasar Alai, and Pasar Bandar Buat using a field-assisted survey approach. The empirical dataset was analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4. The statistical findings reveal that all five structural hypotheses are supported. DVM exerts a powerful, significant direct effect on both Perceived Ease of Use (PEOU) (β= 0.542) and Perceived Usefulness (PU) β= 0.315). Furthermore, PEOU and PU significantly dictate actual platform adoption, with the model explaining 58.4% of the total variance (R2 = 0.584). These results demonstrate that intuitive, empathetic front-end visual ergonomics serve as a vital cognitive gateway that reduces operational friction and drives long-term continuous digital workflow internalization for micro-vendors.